Severe acute respiratory failure due to a multifactorial diffuse alveolar haemorrhage. Issue 3 (8th March 2020) - Crisafulli, Ernesto; Burgazzi, Barbara; Majori, Maria; Serra, Walter; Chetta, Alfredo
Abstract : Diffuse alveolar haemorrhage (DAH) is a life‐threatening syndrome caused by infection, coagulation disorders or autoimmune diseases. We here report the case of an 81‐year‐old male subject affected by a multifactorial DAH, in which the bleeding was related to the administration of clopidogrel and warfarin, both implicated in the context of a polycythaemia. He developed a severe acute respiratory failure treated with a ventilatory support by means of a continuous positive airway pressure (C‐PAP) therapy. An improvement of patient's clinical conditions was observed only after clopidogrel and warfarin discontinuation. Abstract : We here report the case of an 81‐year‐old male subject affected by a multifactorial diffuse alveolar haemorrhage (DAH), in which the bleeding was related to the administration of clopidogrel and warfarin, both implicated in the context of a polycythaemia. He developed a severe acute respiratory failure treated with a ventilatory support by means of a continuous positive airway pressure (C‐PAP) therapy. An improvement of patient's clinical conditions was observed only after clopidogrel and warfarin discontinuation.